Interplay of spectral components in timing properties of accreting compact objects - Alexandra Veledina (Oxford University Press, 2022)
X-ray variability of accreting black hole binaries is believed to be produced by the fluctuations propagating towards the compact object. Observations suggest the light curves in different energy bands are connected, but the fluctuations at harder energies are delayed with respect to the softer ones. The standard interpretation involves dependence of the X-ray spectral hardness on the radial distance, with harder spectra emitted closer to the black hole. Recently, a number of challenges to this scenario have been found, both at qualitative and quantitative level. The model does not predict the large magnitude of the delay between different energies, as well as the dependence of variability amplitude on the spectral range and frequency. We study timing properties of accreting black hole X-ray binaries taking into account peculiarities of spectral formation in these sources. We show that the simultaneous presence of two components leads to a complex shape of power spectra and phase lags between the X-ray bands: the amplitude of the phase lag becomes independent of the delay between the components, and the power spectra show an artificial decrease or, on the contrary, enhancement of power at low Fourier frequencies. This provides an essential ingredient for the reinstatement of the propagating fluctuations model. The work draws attention to the importance of considering conditions of spectral formation when studying timing properties.